Aspects of the reproductive biology of Brassavola cebolleta Rchb.f. (Orchidaceae) - doi: 10.4025/actascibiolsci.v32i4.7148 - André Rodrigo Rech; Yara Brito Chaim Jardim Rosa; Fátima Cristina de Lazari Manente-Balestieri (Acta Scientiarum. Biological Sciences, 2010)
This survey assessed some aspects of the reproductive biology of Brassavola cebolleta Rchb. f. (Orchidaceae) in the Municipality of Dourados, Mato Grosso do Sul State, Brazil. Floral biology, breeding systems, floral visitors and seed germination were analyzed. Differential success and fruit production rate were calculated. Pollination system indicated the pollen vector dependence and absence of pre-zygotic barriers related to self-incompatibility. Pollination occurred at night, being the potential pollen vector a Lepidoptera-Notodontidae of the genus Hemiceras. Differential success of male was 19%, female 9%, and the rate of effective fructification was 6.3%. Fruits produced after pollinator visits were larger than those generated by manual cross pollination, and despite the lower number of potentially viable seeds produced by the first, they presented a higher germination rate in asymbiotic media. This study warns to the vulnerability of the studied species, since the habitat fragmentation associated with pollinator scarcity and seed predation may significantly decrease new recruitment into populations.